WATER SECURITY THROUGH CORPORATE SOCIAL RESPONSIBILITY: A CASE STUDY OF RO WATER PLANTS BY TATA POWER DDL - Kumar, Vikramendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Water security is one of the most pressing issues in urban India especially for the poor. The purpose of this research is to examine the CSR approach to water security focusing on Tata Power DDL’s RO Water Plants in North and North-West Delhi. In this research, I follow the ethnographic method to analyze the effects of Tata Power DDL’s CSR program on JJ colonies’ access to clean drinking water for the targeted beneficiaries. Questionnaires, interviews, and observation were used to measure the social, economic and environmental impacts of the initiative. According to the result, there were changes in health, hygiene, and satisfactions of the community because of safe drinking water source. However, the following was noted as comprising the challenges that CfPTs face: technological barriers; and difficulty in engaging with the community. The study also underlines the significance of public private partnership in water security and provides an insight into how such other CSR programs could be expanded. The study offers important information about the role of CSR in supporting sustainable development and water management in large cities.